A single nucleotide substitution in the SlMCT gene contributes to great morphological alternations in tomato - Mengyi Yu; Yinge Xie; Zilin Qian; Yu Zhong; Huolin Shen; Wencai Yang (Molecular Horticulture)
Abstract Terpenoids, a group of metabolites, are important to plant development and color formation, and serve as valuable nutrients for humans. The enzyme 4-diphosphocytidyl- 2 C-methyl-D-erythritol cytidyltransferase (MCT) plays a pivotal role in the methylerythritol phosphate (MEP) pathway for terpenoid biosynthesis. However, the potential lethality of MCT mutants has hindered further exploration into its functional role in terpenoid metabolite families in plants. Here, we characterized a rare MCT mutant yfm with dwarfism, chlorosis, small leaves, and yellow fruits in tomato. Map-based cloning and sequence analysis revealed that a single nucleotide substitution in the SlMCT gene, which resulted in a point mutation (Leu297Pro) in amino acid in the mutant. Over-expression and complementation of the wild-type SlMCT T in the yfm mutant restored the fruit color and the other defective phenotypes. This mutation altered the gene expressions and metabolic components in the MEP and other pathways. Consequently, the total contents of carotenoids, chlorophyll, IAA, GAs, and SA were decreased, while the contents of CK, JA, and ABA were increased. Eventually, these alterations led to changes in plant phenotypes and fruit color in yfm. These findings provide novel insights into understanding the roles of MCT on plant development and pigment biosynthesis.